O prazer de ouvir rock and roll: uma análise sob a perspectiva do receptor - Invernizzi, Rodrigo Candido (2017)
The dissertation in question aims at a look at rock and roll with a focus on the listener and on the possible auditory sensations and brain connections occasioned at the moment when the music reaches the receiver. Based on the theoretical discussion about the possibilities of analyzing a work, based on Imbert (1987), we seek to understand where such a fascination for rock and roll comes from, especially the work Rock around the clock (understood here as the music that inaugurates the rock and roll genre). The work methodology consisted of a bibliographical review aiming to contribute with analyzes about the musical genre studied. In order to do so, we initially used the analytical approaches systematized by Imbert (1987), and then, in a second moment, to focus on the analysis of the reception, by the jakobsonian model, of the cultural industry and the imaginary. Finally, we observed the act of fruition, which involved diving into the field of acoustics and psychoacoustics, based on Schafer (1977). It was verified that: the function, the meanings and the feelings attributed to the music also arise from the biological conditions and not only from the socio-cultural references of the artist. In addition, both the acoustic context and the soundscape play important roles in the construction of musical reception theory. Finally, it is suggested the comprehensiveness of the analyzes about rock and roll and the receiver of this musical genre.